Extreme Orographic Rainfall in the Eastern Andes Tied to Cold Air Intrusions - Eghdami, Masih; Barros, Ana P. (Frontiers in Environmental Science, 2019)
Long-duration localized heavy rainfall (> 6 hours, < 10 km2) was recorded by raingauges on October 4, 2013 at mid-elevations (~1,500 m) in the Peruvian Andes, which was not apparent in infrared or microwave measurements from either geostationary or polar orbiting satellites. This spring event is investigated here through a numerical modeling study using the Weather and Research Forecasting (WRF) model, and examined in the context of the climatology of Cold Air Intrusions (CAIs) along the eastern flanks of the tropical Andes. The model results suggest significant precipitation enhancement from intense shallow convection at the CAI frontal boundary amplified by orographic lifting as it propagates northward latched to the slopes of Andes. Analysis of CAI mesoscale dynamics was conducted using four decades of European Center Medium-Range Weather Forecasts (ECMWF) reanalysis, Tropical Rainfall Measurement Mission (TRMM) data products, and rain-gauge observations with emphasis on characterizing year-round CAI frequency, CAI interactions with Andes topography, and their impact on orographic precipitation climatology. The data show a robust enhancement of the diurnal cycle of precipitation during CAI events in all seasons, and in particular increases in surface rainfall rate during early morning at intermediate elevations (~ 1,500 m), that is the eastern Andes orographic maximum. This link between CAI frequency and rainfall suggests that they play an important role in maintaining the Andes to Amazon year-round terrestrial connectivity through runoff production and transport by the river networks.